Cost and return of paddy cultivation in Erode district, Tamil Nadu - Manikandan, M; Mani, N; Karthikeyan, P (ORYZA-An International Journal of Rice, 2018)
This study was on cost and return analysis in major paddy production area in selected villages of Erode District, Tamil Nadu. Specifically, the study described the socioeconomic characteristics of paddy farmers, estimated costs and returns from production and examined socioeconomic factors affecting paddy production in the area. The sample farmers in this revenue village were randomly selected from the list of framers in the revenue village. The random sampling technique was employed to obtained primary data from hundred respondents (100) with the aid of a well-structured questionnaire. Conventional percentage method, average method, standard deviation, co-efficient of variation and analysis of variance were employed for the analysis of cost and returns data. The study revealed that paddy production in the area was heavy expenditure on transplantation, fertilizer application; manure application, ploughing and irrigation. After harvest cultivation activities consume a significant part of the expenditure incurred towards paddy production. Caste and size of land holding were the significant factors that affected cost of paddy production in the study area, other factor viz., education showed no variation in the cost of cultivation. However the net returns received by the paddy farmers varied across all the socio economic factors. The net return received from paddy cultivation is comparatively at a very low level as compared with that of the net return obtained from other commercial crop. The study recommended that the increase in the price of fertilizer is the reason for higher cost incurred towards fertilizers application. Hence, fertilizer price must be reduced through government subsidy or farmers can switch over to organic manures use which will reduce the cost in paddy cultivation.Â